The Psychological Consequences of Bureaucratization - Mises, Ludwig von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this work, the author discusses the psychological consequences of preferring a social and economic environment characterized by bureaucratic organization instead of a rational economic organization based on market prices. In the case of a social and economic life characterized by increasing bureaucratization, the paternalistic tutelage tends to become authoritarian and unfavorable to the strengthening of the critical sense, without which a false belief emerges, the idea that it is possible to have liberty under a system of complete regimentation.